Personal Nicknames in Donji Ljubeš near Aleksinac - Stefanović, Dušan R. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
This research study focuses on the male and female nicknames recorded in the village Donji Ljubeš, located near Aleksinac. The nicknames are analysed from the aspect of motivation and classified into twelve groups. Criteria to determine the motivation were received from local residents. In this field research, 160 personal nicknames were collected. There are 139 male and 21 female nicknames. As a contribution to the work, a dictionary of nicknames was compiled. The collected material was accentually and semantically processed. Considering that the research of this kind in the area of Aleksinačko Pomoravlje is in deficit, this study can significantly contribute to the onomastics of the given area.
Keywords: onomastics; anthroponomy; personal nicknames; Donji Ljubeš; Pomoravlje of Aleksinac; Prizren-Timok dialect